Cyclosporin A-induced autoimmunity: the result of defective de novo T-cell development - Damoiseaux, J G; van Breda Vriesman, P J (Folia biologica, 1998)
Cyclosporin A-induced autoimmunity (CsA-AI) is an autoimmune disease, caused by the combinatory treatment with irradiation and cyclosporin A (CsA). CsA-AI is the result of defective T-cell maturation leading to disturbed T-cell balances in the periphery. Increases in Th1 cells and reduction of autoregulatory cells eventually enable the enumerated autoreactive CD4 and CD8 T cells to disturb the homeostasis in the target organs. In unravelling the effect of CsA on T-cell maturation and the role of T cells in CsA-AI many pieces have been put in their places; nevertheless, some remain the topic of debate. The identity of the autoantigen(s) remains elusive, the working mechanism of the autoregulatory cells still is to be determined, and the interplay between CD4 and CD8 T-cell subsets in relation to type-1 and type-2 responses is a matter of interest. In spite of all these unknowns, the CsA-AI autoimmune model is, in contrast to many autoimmune models induced by immunization with a foreign protein in adjuvant, an interesting physiological model based on defective T-cell development including aberrant selection in the thymus and disturbed T-cell balances in the periphery.
Keywords: Autoimmune Diseases; Autoimmunity; thymus; biologické modely; buněčná diferenciace; lidé; Models, Biological; autoimunita; Cell Differentiation; Animals; T-Lymphocyte Subsets; autoimunitní nemoci; Humans; cyklosporin; imunosupresiva; Thymus Gland; T-lymfocyty - podskupiny; Immunosuppressive Agents; Cyclosporine; zvířata